Managing Conflict in Nepali Schools: Educational Leaders' Experiences and Negotiation Practices - Bista, Shreesha; Niraula, Gyanu; Subha, Manika; Paudel, Purna Prasad; Koirala, Shova; Gurung, Sushma (Okhaldhunga Journal, 2026)
In this article, we explore how educational leaders experience and respond to conflict in their everyday school contexts. For this, we conducted a qualitative study using narrative inquiry within an interpretive paradigm, and we collected information through in-depth interviews with four educational leaders from government and private schools in Chitwan, Dharan and Surkhet, selected through convenience sampling. We then analyzed the interviews thematically to understand how conflicts emerge in schools, how they are interpreted, and managed. The findings suggest that school leaders often struggle to clearly identify and manage conflicts in their institutions. Many leaders rely heavily on personal judgment and experience rather than formal policies or structured negotiation strategies. Challenges such as weak communication and limited active listening, ego clashes, unclear conflict-resolution mechanisms, lack of professional training in negotiation, and ongoing resource constraints shape the type of conflicts in schools. We learnt that conflict is not always perceived as a problem. When approached thoughtfully, it can open spaces for dialogue, reflection, and overall institutional growth. The study highlights the need for transformational leadership practices, clear policies, open communication, teamwork in negotiation, and formal training in conflict management to help school leaders move from merely handling conflict to using it as a tool for collaboration and positive change.